ECONOMIC FACTORS AFFECTING THE CONSUMER'S CHOICE OF DENTAL SERVICES (Singaporean Journal of Business Economics and Management, 2021)
Considering the importance of health in the development of communities, in this study, the economic factors affecting the consumer's choice of different dental services are investigated. In this regard, 450 patients referred to dental clinics in Tehran were selected as a sample, and the economic factors affecting consumer's choice of different dental services were analyzed using the Heckman two-step model. The results indicate that income and level of education are among the most important factors influencing the choice of dental services, especially luxury dental services (from the consumer's perspective) such as dentures, scaling, and dental and surgeries. The cost of each of the essential dental services (from the consumer's perspective) such as tooth extraction, tooth restoration, and endodontic therapy does not affect the demand for these services because the coefficient was high in these cases. This means that the consumer often does not pay attention to the cost of essential dental services because he/she has to undergo treatment.